PENGARUH PROFITABILITAS, NILAI PERUSAHAAN DAN LEVERAGE TERHADAP INCOME SMOOTHING PADA PERUSAHAAN CONSUMER CYCLICALS YANG TERDAFTAR DI INDEKS SAHAM SYARIAH INDONESIA (ISSI) TAHUN 2020-2022 - Maryam Saputri, Andi; Orinaldi, Mohammad; Faturahman (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2024)
This study aims to investigate the effect of Pofitability, Firm Value and Leverage on Income Smoothing in Consumer Cyclicals companies listed on the Indonesian Sharia Stock Index (ISSI) for 2020-2022. This study uses secondary data in the form of company annual reports that are the samples in the study and can be obtained from the Indonesia Stock Exchange's website. Samples were taken using a purposive sampling technique, totaling 21 companies. The data analysis technique used is descriptive statistics, classical assumption test, multiple linear regression analysis, and hypothesis testing. Based on the results of the study, it shows that profitability and leverage partially have a significant effect on Income Smoothing, while Firm Value partially cannot have a significant effect on Income Smoothing. Then simultaneously Profitability, Firm Value, and Leverage can have a significant effect on Income Smoothing. The magnitude of the simultaneous effect is indicated by the R square value of 1.7%.